2016
DOI: 10.1542/peds.2015-2901
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Tax Increase and Infant Mortality

Abstract: BACKGROUND AND OBJECTIVE: Maternal smoking increases the risk for preterm birth, low birth weight, and sudden infant death syndrome, which are all causes of infant mortality. Our objective was to evaluate if changes in cigarette taxes and prices over time in the United States were associated with a decrease in infant mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 27 publications
1
38
0
3
Order By: Relevance
“…After removal of duplicates, 12 392 unique citations were screened by title and abstract, and 65 full texts were sourced. Of these, 41 EPOC studies 16 , 17 , 18 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and three non-EPOC studies 65 , 66 , 67 fit the inclusion criteria ( figure 1 ; appendix, pp 6, 7 ). The EPOC studies included data from more than 57 million births, and from 4·6 million GP diagnoses and 2·7 million hospital admissions for respiratory conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, 12 392 unique citations were screened by title and abstract, and 65 full texts were sourced. Of these, 41 EPOC studies 16 , 17 , 18 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and three non-EPOC studies 65 , 66 , 67 fit the inclusion criteria ( figure 1 ; appendix, pp 6, 7 ). The EPOC studies included data from more than 57 million births, and from 4·6 million GP diagnoses and 2·7 million hospital admissions for respiratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The appendix (pp 8–20) details the main characteristics of the EPOC studies. Among these, 26 were interrupted time series studies, 16 , 17 , 18 , 19 , 31 , 32 , 37 , 38 , 40 , 42 , 43 , 45 , 46 , 48 , 50 , 51 , 52 , 54 , 55 , 57 , 58 , 59 , 61 , 62 , 63 , 64 14 were controlled interrupted time series studies, 28 , 29 , 33 , 34 , 35 , 36 , 39 , 41 , 44 , 47 , 49 , 53 , 56 , 60 and one had a regression discontinuity design, 30 a quasi-experimental design bearing close resemblance to interrupted time series methodology. 68 The three non-EPOC studies were uncontrolled before-and-after studies ( appendix, p 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a direct relationship between the rate of deliveries assisted by skilled birth attendants and the proportion of children fully immunized and negatively correlated with maternal, infant, and under-five mortality rates (25). The study by Patrick showed that changing economic status in the United States was associated with infant mortality rate (26).…”
Section: Discussionmentioning
confidence: 99%
“…A US study compared state‐based data from 1999‐2010 on cigarette tax and price with infant mortality, sub‐divided by race, using time‐series models. The data were controlled for income, educational level, time trends and random effects. From 1999 through 2010, the mean overall US infant mortality rate decreased from 7.3 to 6.2 per 1000 live births.…”
mentioning
confidence: 99%